Design and Analysis of Target Simulator Using All Spherical System with High Matching Rate - Shijie Li; Xiaojing Zhang; Kai Zhao; Zihuai Li; Xiong Li; Lumin Zhao; Jin Zhang; Changlong Cai (International Journal of Optics)
To achieve low wavefront error and high throughput with vignetting-free target simulators, a concave-convex-concaveoff-axis spherical system is designed in this paper, which effectively eliminates astigmatism and coma of the system by fields of view (FOVs) and aperture offset and provides theoretical basis for the realization of 100% matching between the exit pupil of the field lens and entrance pupil of the three-mirror anastigmat (TMA) system. Only spherical mirror element is used in this target simulator, which not only reduces the difficulty of manufacturing and cost but also greatly reduces the difficulty of assembling and adjusting. It provides an effective scheme for the design of target simulator and has strong engineering application value.